Work-life conflict towards organizational commitment at Penjara Simpang Renggam, Johor / Famizah Asyikin Azman - Azman, Famizah Asyikin (Faculty of Business and Management, 2012)
Work-life conflict or as known as work-family conflict is one of the conflict that normally happen for those who had married. This conflict happen because the individual need to play the important role at one time. Basically this conflict is normally face by working parents which they must play both role. If they are not systematically allocate their time, they could not able to perform that role. In work-life conflict, there are element that relate to that particular conflict such as time, strain and behavior, workloads, parental demands and family support. This research is conducted in order to see the effect towards organizational commitment. Therefore, this research is being conducted at Penjara Simpang Renggam, Johor which this organization is in public sector. At the end of this research, there is some recommendation will be recommend in order to reduce the particular conflict become bigger and worse.